Remote Monitoring of Perforator Flaps Using an Innovative Device with an Application for Mobile Phone: A Pilot Study - de la Parra, Miguel; Montaño, Javier (Journal of Reconstructive Microsurgery Open, 2017)
Background Surveillance and monitoring of perforator flaps has been well established for many years as a reliable method to detect early changes in the blood flow of the flap. In this manner, early flap revisions could be performed in cases of probable thrombosis.Methods We performed a pilot study that included the first 12 patients to use this device. A temperature sensor electrode was used for remote monitoring of perforator flaps using a mobile phone in real time via a general pocket radio service and short messages developed by the authors, allowing the surgeon to check the temperature from any location.Results The device continually displays the temperature of the flaps in real time performing a curve with measurements every 5 minute using the web page. A significant difference (p < 0.05) is shown between flaps with sufficient flow and flaps with venous thrombosis.Conclusion Real-time direct thermography via the surgeon's mobile phone is a reliable method for flap monitoring, facilitating monitorization during the time when the surgeon is away from the hospital.
Keywords: perforator flaps; remote monitoring; mobile device